A EDUCAÇÃO DE BASE E OS DIREITOS NO EXERCÍCIO DA CIDADANIA - Carvalho, Talita Aparecida Leite; Morato, Roger Wallace; Munhoz, Fabiana Mansueto; Silva, Ana Paula Pereira; Silva, Eliclenes Rodrigues; Santos, Edson Quirino dos; Pinna, Regina Maria (Revista Ciências Jurídicas e Sociais - UNG-Ser, 2014)
... ver o texto na íntegra.